Peluang dan Hambatan Dinas Komunikasi Informatika Statistik dan Persandian dalam mendukung program pembangunan Gubernur Sulawesi Selatan (2018-2023) - Andi Baso Achmad Pangerah; Hafied Cangara; Arianto (Syntax Corporation, 2023)
The world of global information is experiencing very rapid development, which is marked by the massive and widespread use of information and communication technology by the public and makes it easier for state administrators to serve the community. Enhancement of quality management based on technology, information, and communication is the wrong effort by the government to create transparency and not quite enough to answer maintenance. Matter This is required to increase the ability of the government to provide services to the public. The priority program of the South Sulawesi Provincial Communication Informatics and Encoding Office in an effort to support the vision and mission of the Governor of South Sulawesi in the Regional Medium Term Development Plan (RPJMD) of the South Sulawesi Province is